TEACHERS’ CREATIVITY IN USING DIGITAL LEARNING MEDIA DURING THE COVID 19 PANDEMIC AT SMP NEGERI 13 MAKASSAR - Zamzani, Aulia; Anugrawati, Nunung; Junaid (FKIP Unismuh Makassar, 2022)
This research aimed to find out the form of teachers’ creativity in using digital learning media during the COVID 19 pandemic, the problems that faced by teacher in using digital learning media and how the teacher overcome the problem in using digital learning media. Three English teachers from SMP Negeri 13 Makassar were the subjects of the study. The method used was descriptive qualitative research that describes teachers’ creativity in using digital learning media during the covid 19 pandemic. The researcher used observation and interviews as an instrument in data collection. In analyzing the data, the researcher used three steps, the first was data reduction, the second was data display, and the last was data verification. The result of the analysis showed that the English teacher has three forms of creativity. The first fluency was teachers have the initiative and idea in using digital learning media. The second is flexibility, teachers have varied ideas in terms of combining the media. And the last originality, teacher has been unable to create new media. With limited abilities, teachers tend still to use the available media. On the other hands, the problem faced by the teachers in using digital learning media was signal interference which caused the learning process stop, and not all students have smartphones, so learning was not optimal. Meanwhile, the way to overcome problems in using digital media was to make learning videos that can be accessed even when the internet was down, so that students view the material without fear of signal interference. Regarding students who do not have smartphones, the teacher provides flexible time for students to take part in learning.